IMPROVING FARMERS' HEALTH THROUGH EDUCATION AND EARLY DETECTION OF NON-COMMUNICABLE DISEASES IN CIOYOD VILLAGE, BAYONGBONG, GARUT - Nurani Ai Erlinawati Nurani Ai Erlinawati; Andhika Lungguh Perceka Andhika Lungguh Perceka; Hasbi Taobah Ramdani Hasbi Taobah Ramdani; Sugiah Sugiah; Herlin Rusyani Herlin Rusyani; Taufik Huda Taufik Huda (LP4M STIKes Karsa Husada Garut, 2025)
Farmers are a community group that is vulnerable to non-communicablediseases (NCDs) due to heavy physical work, environmental exposure, and lowliteracy and access to health services. Non-communicable diseases oftendevelop without early symptoms, so many cases are not detected early on. Thisactivity aims to improve the health status of farmers through health educationand early detection of non-communicable diseases in Kampung Cioyod,Bayongbong District, Garut Regency. The implementation method uses apromotive and preventive approach based on community empowerment,which includes the stages of preparation, health education, early detection ofNCDs, health counseling, and monitoring and evaluation. Health education wasconducted interactively to increase farmers' knowledge and awareness of riskfactors, prevention, and control of NCDs. Early detection was carried outthrough blood pressure checks, blood sugar level tests, and body mass indexmeasurements. The results of the activity showed an increase in farmers'knowledge and positive attitudes towards healthy living behaviors, as well asthe discovery of farmers with risk factors and early indications of NCDs thatwere previously unknown. This activity is effective in increasing healthawareness and early detection of NCDs among farmers, and has the potentialto improve productivity and community welfare in a sustainable manner.